Rationality Actions of KJA (Floating Net Cage) Workers After the Tubo Sulfur Disaster in Nagari Koto Malintang, Tanjung Raya District, Agam Regency - Fadhila Rahma Purwanti; Irwan Irwan; Ikhsan Muharma Putra (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
The tubo sulfur disaster resulted in material and non-material losses for the people in Nagari Koto Malintang. The tubo sulfur disaster occurs every year so that people have to find new jobs so that their daily needs can be met. The purpose of this study was to analyze the rationality of KJA workers (floating net cages) after the tubo sulfur disaster in Nagari Koto Malintang, Tanjung Raya District, Agam Regency. The theory used in this study is the theory of rationality action put forward by Max Weber. This research was conducted in Nagari Koto Malintang, Tanjung Raya District, Agam Regency. This study used a qualitative research method with a descriptive research type. Withdrawal of informants was carried out using a purposive sampling technique, with the informants being people who live around Nagari Koto Malintang, Tanjung Raya District, Agam Regency. The data collection method in this study begins with document studies, interviews, and non-participant observations. Data analysis used the Milles and Huberman model which was carried out in several stages, namely data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the people of Nagari Koto Malintang, Tanjung Raya District, Agam Regency, who experienced disaster pressure in the form of tubo sulfur, took actions to maintain the household economy, called rationality actions. The rationality of floating net cage workers is the act of clearing agricultural land, the actions of service workers as an act of rationality which includes working as a public transportation driver, travel driver and as a farmhand, and the act of taking advantage of those closest to them.